The Icefield Ranges Research Project, 1975 And 1976 - de la Barre, Kenneth (ARCTIC, 1977)
During 1975 and 1976, research staff and students occupied the base camp of the Icefield Ranges Research Project (IRRP) at Kluane Lake (61 N, 138 30 W) from early April to mid-October. Altogether 126 individuals representing universities and institutes in Canada and the United States made use of the field research facilities during these two years. A decrease from 3,200 mandays of accommodation and subsistence in 1975 to 2,799 in 1976 reflected increasing difficulties in obtaining funds for field research in the North. Adverse weather in the St. Elias Mountains in 1975 caused several projects to be severely restricted. Poor radio conditions and aircraft operational problems provided further difficulties. At one time both of AINA's ski-equiped Helio-Courier aircraft were out of commission. . In 1976, however, generally good weather conditions prevailed, radio communications were vastly improved, the aircraft remained airborne and the projects prospered. Several improvements were made to the base camp itself. . In cooperation with Parks Canada and Environment Canada, a year-round meteorological programme was carried out during 1975 and 1976 at the base camp by the camp Manager, A. Williams. . [The following research programs are described: High Altitude Physiology Studies (HAPS), Glacier inventory of St. Elias Mountains, Glacier geophysics projects, Environmental controls on geomorphic processes, and Study of small mammals.]